2012
DOI: 10.1007/s00262-012-1260-2
|View full text |Cite
|
Sign up to set email alerts
|

Autologous cytokine-induced killer cell immunotherapy in lung cancer: a phase II clinical study

Abstract: The data suggested that CIK cell immunotherapy could improve the efficacy of conventional chemotherapy in NSCLC patients, and increased frequency of CIK cell treatment could further enhance the beneficial effects. A multi-center randomized trial is being carried out in our hospital to further validate these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
78
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(83 citation statements)
references
References 33 publications
4
78
1
Order By: Relevance
“…In this study, after 5 courses, immune function improvement rates could all be over 70%, consistent with the report of Li et al (2012) on kidney cancer immune function improvement. This study suggested that the improvements of immune function by CIK cells were affected by two factors, the first factor was the situation of immune function of lung cancer patients prior to the treatment, different immune functional status would react differently to CIK therapy.…”
Section: Discussionsupporting
confidence: 78%
“…In this study, after 5 courses, immune function improvement rates could all be over 70%, consistent with the report of Li et al (2012) on kidney cancer immune function improvement. This study suggested that the improvements of immune function by CIK cells were affected by two factors, the first factor was the situation of immune function of lung cancer patients prior to the treatment, different immune functional status would react differently to CIK therapy.…”
Section: Discussionsupporting
confidence: 78%
“…On the other hand, CIK cell infusion can improve the immune function of patients, which was consistent with other studies [27][28][29][30], indicating that maintaining and enhancing immune functions played a crucial role in improving quality of life and survival in lung cancer patients. There was only 1 case of mild fever in treatment group after treatment, while the patient could relieve by symptomatic treatment.…”
Section: Discussionsupporting
confidence: 78%
“…This result is similar to the findings of Li et al, who also report that CIK cell treatment can improve the efficacy of chemotherapy in NSCLC patients. 24 More importantly, our results suggested that patients who received alternate CIK and NK cells treatment exhibited a better prognosis than those who received CIK cells only. These results indicate that adjuvant CIT, especially with the alternate application of CIK and NK cells, can improve the clinical outcome of NSCLC patients.…”
Section: Discussionmentioning
confidence: 49%
“…Indeed, previous studies have increasingly confirmed the positive clinical efficacy of CIT in the treatment of NSCLC. [22][23][24][25][26] However, to date, the patterns of CIT have been rarely reported. Therefore, in the present study, through a retrospective analysis of 120 patients with NSCLC, we not only validated the efficacy of adjuvant CIT combined with chemotherapy, but also found that the efficacy of adjuvant CIT with alternate application of CIK and NK cells were superior to that of adjuvant CIT with CIK cells only.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation